The Miserly Of Ebenezer Scrooge Reflectedat Charles Dickens's A Christmas Carolnovel (1843): A Sociological Approach - Miyati, Tina Islam; , Drs. Abdillah Nugroho, M. Hum; , Nur Hidayat, M.Pd (2014)
The major problem of this research is how the miserly character of Ebenezer Scrooge reflected at Charles Dickens's A Christmas Carol novel. It is conducted by analyzing the novel based on the structural elements and analyzing some aspects in England society in the nineteenth century based on sociological approach. This research is qualitative research. Type of the data of the study is text taken from two data sources; primary and secondary data sources. The primary data source is A Christmas Carol novel written by Charles Dickens in 1843. While the secondary data sources are other materials taken from A Christmas Carol film 3D, books, essey articles, internet and other relevant information. Both data are collected through library research and analyzed by descriptive analysis. Based on the analysis the researcher draws the following conclusions. First, based on the structural analysis of each element, it shows that the character and characterization, setting, plot, point of view, style and theme are related to each other and form the unity into good quality of the novel. Second, based on the sociological analysis, there is a close relationship between the novel story and the reality of England life. This novel describes the social effect from the Scrooge's character. The social status of main character in this novel can aliterate the bad character (miserly) into good character (generousity) with the way visited by three Spirits.